2017
DOI: 10.1155/2017/2356346
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Therapeutic Exercise in Fibromyalgia Syndrome: A Systematic Review and Meta-Analysis of Randomized Clinical Trials

Abstract: Objective The aim of this study was to summarize evidence on the effectiveness of therapeutic exercise in Fibromyalgia Syndrome. Design Studies retrieved from the Cochrane Plus, PEDro, and Pubmed databases were systematically reviewed. Randomized controlled trials and meta-analyses involving adults with fibromyalgia were included. The primary outcomes considered in this systematic review were pain, global well-being, symptoms of depression, and health-related quality of life. Results Effects were summarized us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
154
1
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(176 citation statements)
references
References 26 publications
6
154
1
15
Order By: Relevance
“…The treatment of pain in FM has focussed on pharmacotherapy and non‐pharmacological treatments such as educating the patients, PA, and educational‐psychological programs shown to be effective in the relief of the symptoms of FM . There are enough evidences that physical exercise is an effective instrument for improving physical fitness, health, and quality of life and causes beneficial effects on the symptoms of FM patients . Overall, studies have reported short‐term improvements in pain, quality of life, and physical fitness, although more studies are needed about the long‐term effects.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The treatment of pain in FM has focussed on pharmacotherapy and non‐pharmacological treatments such as educating the patients, PA, and educational‐psychological programs shown to be effective in the relief of the symptoms of FM . There are enough evidences that physical exercise is an effective instrument for improving physical fitness, health, and quality of life and causes beneficial effects on the symptoms of FM patients . Overall, studies have reported short‐term improvements in pain, quality of life, and physical fitness, although more studies are needed about the long‐term effects.…”
Section: Introductionmentioning
confidence: 97%
“…12 There are enough evidences that physical exercise is an effective instrument for improving physical fitness, health, and quality of life and causes beneficial effects on the symptoms of FM patients. [13][14][15][16][17] Overall, studies have reported short-term improvements in pain, quality of life, and physical fitness, 18 although more studies are needed about the long-term effects. However, despite these benefits, a high dropout rate in PA programs is commonly observed among the patients with FM, and a low percentage of patients comply with the weekly PA recommendations.…”
mentioning
confidence: 99%
“…FM is characterized by widespread pain, along with multiple other symptoms including fatigue and cognitive fog [53][54][55][56][57]. As in CFS, a multidisciplinary approach to management is recommended, often accessed through chronic pain clinics.…”
Section: Comorbid Pain Fatigue and "Cognitive Fog"mentioning
confidence: 99%
“…As in CFS, a multidisciplinary approach to management is recommended, often accessed through chronic pain clinics. This approach may include non-pharmacologic management including education around pacing, CBT and exercise [53,54].…”
Section: Comorbid Pain Fatigue and "Cognitive Fog"mentioning
confidence: 99%
“…Randomized controlled trials (RCTs), testing for the simultaneous combination of ET and CBT, have been shown to be the most effective non-pharmacological treatments for FM [13]. Treatments based exclusively on ET have contributed to the reduction of symptoms of pain, fatigue, and depression, as well as to the improvement of mental health, psychological well-being, and physical function [14,15]. CBT-based treatments have favoured the acceptance of FM, strengthening of self-efficacy, development of coping strategies, and the reduction in depressive moods [16].…”
mentioning
confidence: 99%